SECURING EDGE DEVICES: ESSENTIAL STRATEGIES FOR MODERN CYBERSECURITY - Chintan Udeshi , (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Edge devices have become essential components of modern digital infrastructure, transforming how organizations process data, leading to faster response times for critical applications. From smart vehicles to industrial IoT sensors, edge devices operate outside traditional security perimeters, creating unique cybersecurity challenges. Organizations face increasing threats from data breaches, DDoS attacks, ransomware propagation, and network infiltration through compromised edge devices. The evolving landscape demands comprehensive security strategies, including continuous monitoring, strict access controls, robust software management, zero-trust architectures, and AI-powered security solutions for the applications and infrastructure running on the edge. As edge computing continues to expand, organizations must adapt their security measures to address emerging vulnerabilities while maintaining operational efficiency and regulatory compliance.